Middle East and North Africa Economic Update, April 2010 : Recovering from the Crisis - Ianchovichina, Elena; Mottaghi, Lili; Carey, Kevin; Spivak, Nadia; Farazi, Subika; Silwal, Ani (World Bank, Washington, DC, 2016)
This edition of the Middle East and North Africa (MENA) regional economic update concerns the region recovering from the financial crisis along with the global economy. Growth in 2010 is expected to be 4.4 percent region-wide, driven by domestic absorption as well as a positive contribution from external demand. The recovery from the crisis differs by country depending on initial conditions and the intensity of the impact via the three principal channels through which the global financial crisis affected MENA economies-the financial sector, the price of oil, and the balance of payments, reflecting the impact on trade, remittances and Foreign Direct Investment (FDI) flows. The Gulf Cooperation Council (GCC) countries are leading the regional recovery as oil prices have rebounded and the GCC financial sector is stabilizing. Developing oil exporters felt the impact of the crisis, and now the recovery, largely through the oil price channel, due to the limited integration of their banking sectors into global financial markets and the importance of oil in their exports. The oil importers were affected by the crisis through the secondary effects on trade, remittances, and FDI flows, so their recovery will depend crucially on the recovery in key markets, especially the EU and the GCC countries. High unemployment has been a problem in MENA for years, and the crisis has dimmed prospects for improvements in the near term. Ample oil and gas resources, a youthful and growing workforce, and a growing momentum to look for ways to diversify their economies imply that the growth potential of the region is high, but MENA countries continue to face formidable longer term challenges. Ensuring access to finance without compromising financial stability will be a major challenge in MENA, although issues related to weak regulatory systems, corporate governance and overdependence on the banking system also loom large. Key problems of the business environment in MENA include policy and regulatory uncertainty and discretion in implementing reforms which prevent a level playing field for all firms and encourage the pursuit of privileged access. These problems, coupled with barriers to entry and exit, have created an environment of stagnation. Addressing these issues will require applying rules and regulations consistently and without discrimination among firms and introducing reforms that promote business dynamism, private investment, and innovation.